Impact of resistance training in cancer survivors: a meta-analysis - Prüller-Strasser, Barbara; Steindorf, Karen; Wiskemann, Joachim; Ulrich, Cornelia (Medicine and science in sports and exercise, 2013)
Purpose - Current evidence suggests many health benefits from physical activity during and after cancer treatment. However, the optimal exercise program for cancer survivors has not yet been established. The purpose of this meta-analysis was to summarize evidence for the efficacy of resistance training (RT) interventions to improve muscle strength and body composition among adult cancer survivors. We also investigate potential dose-response relationships between intensity, duration, and frequency of RT and assessed outcomes. - Methods - A systematic literature review of the Clinical Trial Register, Cochrane Trial Register, MEDLINE, and EMBASE literature databases was undertaken. Studies were included if they were randomized controlled trials (RCT) comparing RT with an exercise or nonexercise control group in cancer survivors during and after treatment. Thirteen articles from 11 RCT met our inclusion criteria. We performed a random-effects meta-analysis to determine weighted mean differences (WMD) with 95% confidence intervals using the Cochrane Review Manager 5.0.25. A random-effects metaregression model was performed to examine dose-response relationships between RT variables and assessed outcomes. - Results - Quantitative evidence shows a large effect of RT on lower-limb and upper-limb muscle strength (WMD: +14.57 kg, P = 0.0005 and +6.90 kg, P < 0.00001, respectively) and moderate effects on lean body mass and percentage of body fat (WMD: +1.07 kg, P < 0.0001 and −2.08%, P = 0.003, respectively). A small positive effect of RT was noted on Functional Assessment of Cancer Therapy-Fatigue (P = 0.05). Upper-limb muscle strength and percentage of body fat improved to a greater extent when RT interventions were of low to moderate intensity (≤75% one-repetition maximum, P = 0.042). - Conclusions - RT was shown to be associated with clinically important positive effects on muscular function and body composition in patients during treatment or in long-term follow-up.
Gesehen am 11.03.2022